The "Hub and Spoke" model has no effect on mortality in acute upper gastrointestinal bleeding: A prospective multicenter cohort study. Issue 9 (September 2021) - Marmo, Riccardo; Soncini, Marco; Bucci, Cristina; Zullo, Angelo; ,; Amitrano, L; Anderloni, A; Andriulli, A; Annese, V; Baldassarre, G; Bargiggia, S; Bazzoli, F; et al.
Abstract: Background: the lack of standardized pathways for patients with gastrointestinal bleeding may have led to differences in their management and inequity to medical care access. The "Hub & Spoke" model was adopted to fill this gap in many disciplines, but, to our knowledge, no data exist on its efficacy on mortality in GI bleeding. We aimed to evaluate if the "Hub & Spoke" organizational model has an impact on mortality risk from UGIB. Methods: from January 2014 to December 2015, 3324 consecutive patients admitted for UGIB in 50 Italian hospitals were enrolled (1977 patients in hospitals within the "Hub & Spoke" network for digestive hemorrhagic emergency and 1347 in hospitals outside the "Hub & Spoke" network). Clinical, endoscopic and organizational data were recorded. Results: we observed no differences in mortality between patients admitted to hospitals included or not included in the "Hub & Spoke" network (5.2% vs 6.1%, p = 0.3). On multivariate analysis, admission in gastroenterology wards (OR 0.61, p = 0.001) or an academic hospital (OR 0.65, p < 0.056) were independent protective factors while being in "Hub & Spoke" organization system did not affect mortality (OR 1.09, p = 0.57). Conclusion: the "Hub & Spoke" model per sé does not impact on mortality while being treated in academic hospital or gastroenterology wards improved survival.